Why do I want to become an English teacher? : - Subaşı, Gonca (Anadolu Üniversitesi, 2010)
Teacher education has been subjected to number of research studies over the last thirty years and yet we are still trying to understand why people are attracted into teaching. Such a situation suggests that we need a different approach to understand the factors leading individuals to become teachers. Therefore, the basic purpose of the present study is to develop a valid and reliable instrument measuring motivations of student teachers to enter English teacher education programs. In order to develop such an instrument, first, pre-service English teachers' career motivation needed to be determined. The study was conducted in two phases. In Phase 1, the reasons that motivate pre-service teachers to enter the ELT department were investigated in order to create an item pool that would be used to develop an instrument. A total of 642 students enrolled in the ELT department of Faculty of Education at Anadolu University participated in the first phase of the study. Their motives to become English teachers were identified through the use of various data collection procedures; listing reasons, keeping diaries and interviews to achieve triangulation. The reasons for becoming English teachers reported by the participants in Phase 1 were categorized under several categories supported by literature and the experts in the area, and then transformed into the instrument items. In Phase 2, the instrument in the form of a questionnaire was developed on the basis of the data provided in the first phase and it was administered to a different group of students numbered 800. The validity and reliability of the questionnaire was calculated and it was found out that it could be used as an instrument for measuring the career choice of teaching English in the Turkish context. The outcomes of the study also revealed that understanding the starting points of these student teachers would help the teacher trainers to motivate them during their education in the teaching career.
Keywords: İngilizce öğretmenleri Yetiştirme; İngiliz dili Öğretim